Android Botnets: A Serious Threat to Android Devices - Shahid, Anwar; Mohamad Fadli, Zolkipli; Zakira, Inayat; Odili, Julius Beneoluchi; Ali, Mushtaq; Jasni, Mohamad Zain (Universiti Putra Malaysia, 2018)
Android devices have gained a lot of attention in the last few decades due to several reasons including ease of use, effectiveness, availability and games, among others. To take advantage of Android devices, mobile users have begun installing an increasingly substantial number of Android applications on their devices. Rapid growth in many Android devices and applications has led to security and privacy issues. It has, for instance, opened the way for malicious applications to be installed on the Android devices while downloading different applications for different purposes. This has caused malicious applications to execute illegal operations on the devices that result in malfunction outputs. Android botnets are one of these malfunctions. This paper presents Android botnets in various aspects including their security, architecture, infection vectors and techniques. This paper also evaluates Android botnets by categorising them according to behaviour. Furthermore, it investigates the Android botnets with respect to Android device threats. Finally, we investigate different Android botnet detection techniques in depth with respect to the existing solutions deployed to mitigate Android botnets.